Operation Scheduling for Yarn Production with The Autonomous Distributed Manufacturing Systems (ADiMS) Concept - Febriansyah, Muhammad Zulfahmi; Setia, Fauzi Aji (Universitas Mercu Buana, 2025)
The textile industry is one of the Indonesian priority industries for the Industry 4.0 development program. There are a lot of textile industries still in the Industry 2.0 phase. These industries need to adopt Industry 4.0 concepts without automating the production operation to compete with their rivals. The digital twin and Autonomous Distributed Manufacturing Systems (ADiMS) concept were used to implement Industry 4.0 in this case. The objective of this research is to develop an operation scheduling system that can distribute the yarn manufacturing scheduling task to each workstation in a virtual production system using the ADiMS concept. Every actual manufacturing component in ADiMS is simulated in a virtual production system to interact with one another and make decisions; then a process-based product model is developed to capture all the conditions from yarn production in real production systems. Each production element is modeled as an object in Python programming. The simulation is set up to have 31 machines that are ready to be used for production scheduling and 2 types of products. The operation scheduling system with the Autonomous Distributed Manufacturing Systems (ADiMS) concept for yarn production has been created and simulated in a virtual environment and shown the operation schedule that fits the desired criteria.